Analysis of Rectilinear Snake Robots in ISO 8608 Random Surface - Kanniga, E.; Sindhuja, S. (International Journal of Psychosocial Rehabilitation, 2019)
This paper deals with the analytical modeling of rectilinear snake robots. During recent times, snake robots have created much interest among researchers. The rectilinear pattern gait is one of the four biological snake locomotion modes. . Rectilinear snakes have been widely used in rescue operations, especially in rough terrain, especially in narrow spaces where human intervention is not easy. Computational analysis of rectilinear motion is done using MATLAB for ISO 8608 random surface